PERAN PENGETAHUAN IBU DAN FAKTOR DEMOGRAFI DALAM PELAKSANAAN PROGRAM PENGENDALIAN DIABETES MELITUS PADA ANAK DI KABUPATEN LANGKAT - Lily Putri Marito; Afiatika Ahsani (Program Studi S1/DIII-Keperawatan Universitas Imelda Medan, 2026)
Parental knowledge is an important factor in the success of the Diabetes Mellitus (DM) Control Program in children. A good understanding enables mothers to effectively implement preventive measures, monitoring, and routine management. The aim of this study was to map the level of mothers' knowledge about DM and the DM control program in children, identify barriers to program implementation, and analyze the relationship between mothers' knowledge and demographic factors with the implementation of the DM control program in Langkat District. This study used a quantitative descriptive cross-sectional design with 45 mothers selected through purposive sampling. This research was conducted in March-May 2025 at the Puskesmas Stabat Lama. Data were collected through a structured questionnaire measuring four variables: knowledge of symptom recognition, prevention strategies, blood sugar monitoring, and diet management, as well as program implementation scores. Data analysis was conducted using descriptive statistics, Pearson's correlation test, and analysis of the relationship between demographic factors (age and education) and perceived barriers to implementation. The results showed that mothers' overall knowledge was moderate to high, with the highest scores in blood sugar monitoring and prevention. The main barriers included limited information, time constraints, lack of family support, and practical skills. Correlation analysis showed a moderate positive relationship between mothers' knowledge levels and program implementation (r = 0.452, p = 0.003). The conclusion of this study is that mothers' knowledge of diabetes control programs in children is moderate to high (75.6% - 85%). Several major inhibiting factors in implementing diabetes control programs in children include limited access to information, limited medical and adequate health facilities, and economic hardship.